How do young people with a hereditary cancer predisposition syndrome understand and experience cancer survivorship? "With Li‐Fraumeni syndrome, it's just an intermission". Issue 3 (3rd January 2023) - Werner‐Lin, Allison; Forbes Shepherd, Rowan; Rising, Camella J.; Thompson, Ashley S.; Huelsnitz, Chloe; Wilsnack, Catherine; Boyd, Patrick; Sleight, Alix G.; Hutson, Sadie; Khincha, Payal P.
Abstract: Objectives: Adolescents and young adult (AYA) cancer survivors face unique medical and psychosocial sequalae, including chronic health conditions, late effects of treatment and fear of recurrence. The meaning of cancer survivorship may be further complicated for AYAs with hereditary cancer predisposition syndromes. This study used a patient‐centered framework to investigate how AYAs with Li‐Fraumeni syndrome (LFS) consider cancer survivorship. Methods: An interprofessional team conducted 30 semi‐structured interviews with AYAs (aged 18–41, mean 31 years) enrolled in the National Cancer Institute's LFS Study (NCT01443468). Twenty had experienced at least one cancer diagnosis. Interview data were thematically analyzed by an inter‐professional team using interpretive description and grounded theory methods. Findings: Participants viewed "survivorship" as a period marked by no evidence of formerly diagnosed disease. By contrast, participants felt the label "survivor" was tenuous since LFS is characterized by multiple primary malignancies and uncertainty about intervals between one diagnosis and the next. Many AYAs viewed survivorship as requiring a high degree of suffering. Though many personally rejected "survivor" identities, almost all articulated its various functions including positive, negative, and more complicated connotations. Instead, they chose language to represent a range of beliefs about survival, longevity, prognosis, and activism. Conclusions: AYAs with LFS struggle with the term "survivor" due to their multi‐organ cancer risk, short intervals between malignancies, and evolving identities. Loved ones' cancer‐related suffering informed perspectives on survivorship. Survivorship care for AYAs with cancer risk syndromes requires interprofessional interventions that address their unique biomedical and psychosocial needs.